História agrária da colônia militar do Xapecó: do império a república (1882-1925) - Venson, Leticia Maria (2024)
This study examines the Xapecó Military Colony, with the aim of investigating the land-related issues surrounding the occupation and titling of land in the region where the colony was established between 1882 and 1925. The objective is to explore the various aspects of land ownership and regulation within the former military colony and analyze how both civilian and military settlers gained access to and legitimized their claims to the land. This research employs Carlo Ginzburg's evidential paradigm, a methodology that focuses on uncovering clues and details within historical sources to provide a more nuanced understanding of events. As a theoretical basis, we use Pierre Bourdieu's concepts on the State, Symbolic Power, Region, and Commission. The primary sources used in this study include reports from the Ministry of War, newspapers available through the National Digital Library, documents from the Public Archive of Santa Catarina, and records from the Army Archive. The Xapecó Military Colony, established in the context of territorial disputes with Argentina, encountered significant challenges related to land titling. Although many settlers were granted provisional titles, the failure to validate these documents led to a state of land insecurity. This situation favored large landowners while marginalizing small farmers, perpetuating conflicts that continue to this day. This thesis contributes to the discussion on military occupation and colonization policies in Brazil, emphasizing how the state's territorial management influenced regional development and land distribution in the frontier region of Santa Catarina.